Small insecticidal molecules against crop pests. Issue 10 (3rd October 2018) - Nayyar, Nishtha; Bhatnagar, Raj K.
ABSTRACT: Previous decades have seen excessive use of chemical insecticides to control insect-mediated crop losses. However, toxicological and ecological concerns lead to the quest for more sustainable biological molecules as an alternative. Advent of Bt technology witnessed its supersession over chemical control measures and reinvigorated the potential of bioinsecticides as a commercially viable option. But the development of Bt-resistance in insect populations has raised concerns and entails the invention of alternate measures. In this review, we discuss the recent advancements in the field of Bt toxins and evaluate the potential of other insecticidal proteins and RNAi as the next generation insecticidal technologies.